Can deviation from standard beauty become appealing?: an age perspective - Lima, Mariana Braga de (2015)
When exploring new perspectives on the impact of non-idealized vs. idealized body image in advertising, studies have focused mainly on body size, i.e., thin vs. heavy (Antioco et al., 2012; Smeesters & Mandel, 2006). Age remains largely unexplored, and the vast majority of ads in the market depict young models. The purpose of this research is therefore to investigate which images in advertisements – young or mature models – are more persuasive for older women (40+ years old). In this investigation, two studies were conducted. The first part was an exploratory analysis with a qualitative approach, which in turn helped to formulate the hypothesis tested in the subsequent experiment. The results of the in-depth interviews suggested a conflict over notions of imprisonment (need to follow beauty standards) and freedom (wish to deviate). The results of the experiment showed essentially that among older consumers, ads portraying older models were as persuasive as ads portraying younger models. Limitations and future research are discussed.